The analysis of internal policy implementation on the behaviour of government officer - Lisdawati Muda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
This article aims to analyse the implementation of internal policy on Civil Servant Officer work performance at IAIN Sultan Amai Gorontalo. Internal policy is an urgent item in leading an institution because it guarrantes the individual work performance. The workers will get their good work performance since the internal policy lies on worker side. The method of this research was qualitative descriptive by using field observation and interview as data collection. The data were analyzed into three steps, namely data reduction, data display, and data conclusion. The participants of this research were five administration staff, three lecturers, and five students. It used purposive sampling. The result showed that the implementation of internal policy at IAIN Sultan Amai Gorontalo was not effective. It caused by three problems. Firstly, it is lack of evaluation during the internal policy implemented and after it was implemented. Secondly, it is lack of coordination among stakeholders and the workers (administration staff, lecturers, and the students). Thirdly, it is lack of collaboration among stakeholder and staffs.